Socio-Economic Conditions Of Nutmeg Farmers In Lonthoir Village After Independence 1950-2000 - Muhamad, Puput (ARRUS Journal of Social Sciences and Humanities, 2025)
This study analyzes the economic, social, and cultural dynamics of nutmeg farmers in Lonthoir Village, Banda Island, in the period 1950 to 2000. Using a qualitative approach, this study explores the impact of agrarian policies, fluctuations in international market prices, and modernization on farmers' lives. The findings show that the post-independence land redistribution policy experienced challenges in its implementation, while agricultural modernization during the New Order period benefited the local elite more than smallholder farmers. Farmers adopt diversification strategies and utilize customary systems to survive amid price fluctuations and social changes. The globalization of the spice market has also affected the stability of farmers' incomes, underscoring the importance of government support in protecting local market access. This research provides important insights into the history of agrarian and economic transformation in Indonesia as well as its relevance to rural development policies.